A Comparative study on plasmid isolation from strains of Enterobacter aerogenes using different optimized procedures - Gowri, R.; Kamalini, A.; Thavaranjit, A.C. (University of Jaffna, 2020)
Enterobacter aerogenes are gram negative, facultative anaerobic motile bacteria which possess plasmids. Plasmids are extra chromosomal DNA. Plasmid DNA has been used as the most powerful tool in several molecular and biotechnological applications. In this current study three modified protocols were examined including mini preparation method, hot and cold alkaline lysis method and compared their simplicity, rapidity, costs and plasmid quality for extracting plasmid DNA from bacterial strains of Enterobacter aerogenes from different sources. According to the results obtained all three methods are good and yielded plasmid DNA but each methods has its advantages and disadvantages. Among all three methods, the spectrophotometric highest yield of plasmid DNA (83 ug/uL) was obtained in mini preparation method and lowest yield (20 ng/uL) in cold alkaline lysis method. The best spectrophotometric 260/280 ratio (near to 1.8) also obtained in mini preparation method which indicates the purity of extracted plasmid DNA. Among all three methods tested in this study, Mini preparation method is more efficient, time saving, non-hazardous and less cost method as it doesn’t require any expensive enzymes and hazardous chemicals.
Keywords: Plasmids; DNA extraction; Enterobacter aerogenes; Alkaline lysis; Mini preparation